The Third World approaches to International Law: an analysis of Colombia's main conventions on Human Rights from the perspective of TWAIL (1984-2018) (Revista revoluciones, 2020)
Third World Approaches to International World (TWAIL) are a series of theories or approaches that seek to find options to the Eurocentric and colonialist way as international relations have traditionally been approached. Colombia, being a Latin American and third world country, is doubly conditioned to the policies with which the historical direction of the peoples has been managed. This study aims to make an approach to the agreements and treaties signed by Colombia from 1984 to 2018 in the field of Human Rights from the TWAIL perspective, to determine if they have been complied with and how said treaties and agreements have affected or favored International Relations.
Keywords: TWAIL; Third World; International Law; International Relations of Colombia; Human Rights